New urban housing - French, Hilary (London : Laurence King, 2009)
Terraces and row houses -- Schieflstätte housing complex (Graz, Austria) -- Condensed housing development (South Biesdorf, Berlin, Germany) -- Nieuw Terbregge (Rotterdam, The Netherlands) -- Housing block 16X68 (Ljubljana, Slovenia) -- In-between terrace (Whatcott's Yard, London UK) -- Stuivesantplein housing (Tilburg, The Netherlands) -- Yoakum Street Town Houses (Houston, Texas, USA) -- Housing on the shore of Lake Gooi (Huizen, The Netherlands) -- Quadrangles and courtyards -- Westfield Student Village (Queen Mary College, London, UK) -- La Maquinista (Barcelona, Spain) -- High Cross Road (London, UK) -- Dwellings for young people (Leipzig, Germany) Town House (Wimbergergasse, Vienna, Austria) -- Mondrian Apartments (Sydney, Australia) -- Integrated housing (Ingolstadt, Germany) -- Harold Way Apartments (Hollywood, California, USA) -- Donnybrook Quarter (London, UK) -- City blocks and infill -- Estradenhaus (Berlin, Germany) -- Rue Pelleport apartments (Paris, France) -- Alfonso Reyes 58 Apartments (Mexico City, Mexico) -- Simmonds Hall, MIT (Cambridge, Massachusetts, USA) -- Yerba Buena Lofts (San Francisco, California, USA) -- Housing in Auwiesen (Winterthur, Switzerland) -- D Residential building (Venice, Italy) -- Apartment Building Gasometer B (Vienna, Austria) -- CODAN Shinonome Canal Court, Centre Block, Block i (Koto-ku, Tokyo, Japan) -- Schots 1 + 2 (Groningen, The Netherlands -- Towers and slab blocks -- 173 Perry Street / 165 Charles Street (New York, USA) -- Contemporaine (Chicago, Illinois, USA) -- Housing Tower (Theresienhöhe, Munich, Germany) -- Flower Tower (Paris, France -- Apartments (Maia, Porto, Portugal) -- Macquarie Street Apartments (Aurora Place, Sydney, Australia) -- Social dwellings (Lakua, Vitoria, Spain) -- Sejima Wing (Kitagata Apartments, Gifu Prefecture, Japan) -- Mirador Apartments (Sanchinarro, Madrid, Spain).
boek